Evolusi Teknologi Komprehensif Jaringan Komunikasi Nirkabel Pada Sistem 4G Menuju 7G - Yonoriadi Yonoriadi; Dhira Yatha Bimatha Dharmavid; Rizaldi Akbar (Jurnal Sistem Komputer (SISKOM), 2026)
The evolution of wireless communication networks from 4G to 7G reflects significant transformations in architecture, capacity, and system adaptability to modern digital demands. 4G LTE provides stable mobile broadband with speeds up to 100 Mbps and moderate latency, supporting video streaming, voice communication, data transfer, and reliable digital services. The transition to 5G introduces substantial increases in network capacity, ultra-low latency, and the ability to connect thousands of devices simultaneously through mmWave technology, massive MIMO, and network slicing, enabling real-time applications, autonomous vehicles, and large-scale IoT deployment. 6G emphasizes adaptive networks leveraging artificial intelligence, edge computing, and terahertz communication, projecting speeds up to 1 Tbps with latency below 0.1 ms, alongside improved energy efficiency and security. The 7G concept integrates terrestrial, satellite, and quantum communication networks, utilizing AI and machine learning for automated spectrum management and latency optimization, supporting global services, smart cities, industrial automation, and remote healthcare. This study highlights the need for aligned infrastructure, security, and regulatory strategies to ensure future networks operate efficiently, reliably, and responsively to continuously growing user demands.